A systematic review of tools, languages, and methodologies for mashup development. (18th October 2013) - Paredes‐Valverde, Mario Andrés; Alor‐Hernández, Giner; Rodríguez‐González, Alejandro; Valencia‐García, Rafael; Jiménez‐Domingo, Enrique
Summary Web 2.0 has become a powerful means of transmitting information in a number of fields, such as communication, e‐commerce, and entertainment. Nowadays, companies and organizations transmit specific information through different mechanisms, such as Web feeds and Web services. These data sources enable third parties to incorporate data from service providers into their own applications. On the basis of this understanding, mashups have emerged as a new approach to develop applications and which combine data and resources from heterogeneous sources—such as internal data sources, Web feeds, screen scraping, and Web services—with the aim of solving specific needs. Mashup development involves activities such as accessing heterogeneous sources, combining data from different data sources, and building graphical interfaces. These activities restrict the development of these kinds of applications only to experienced computer users. Today, a number of tools and programming languages are used to help carry out some of the aforementioned activities. These tools and programming languages have features enabling the integration of different technologies in order to solve problems such as data management from different data sources and content publication. If this is taken into account, there is a growing need to learn about the features, advantages, and disadvantages of these tools and programming languages in order to select the tool or language that best fits a specific need and a specific level of knowledge and experience in terms of software development. This paper presents a systematic review and analysis of the tools, programming languages, and software development methodologies involved in mashup development in order to learn more about the features and services provided by mashups. Furthermore, this research also explains the qualitative and quantitative evaluation used for the mashup development tools. The evaluation was performed in order to measure not only the usability of these tools but also the support that they provide for standardized features of Web development that they provide. Finally, new trends in the development of mashups are discussed. Copyright © 2013 John Wiley & Sons, Ltd.